Viewpoint: Mechanisms of Action and Therapeutic Potential of Neurohormetic Phytochemicals - Mark. P. Mattson; Tae Gen Son; Simonetta Camandola (SAGE Publishing, 2007)
The nervous system is of fundamental importance in the adaptive (hormesis) responses of organisms to all types of stress, including environmental "toxins". Phytochemicals present in vegetables and fruits are believed to reduce the risk of several major diseases including cardiovascular disease, cancers and neurodegenerative disorders. Although antioxidant properties have been suggested as the basis of health benefits of phytochemicals, emerging findings suggest a quite different mechanism of action. Many phytochemicals normally function as toxins that protect the plants against insects and other damaging organisms. However, at the relatively low doses consumed by humans and other mammals these same "toxic" phytochemicals activate adaptive cellular stress response pathways that can protect the cells against a variety of adverse conditions. Recent findings have elucidated hormetic mechanisms of action of phytochemicals (e.g., resveratrol, curcumin, sulforaphanes and catechins) using cell culture and animal models of neurological disorders. Examples of hormesis pathways activated by phytochemicals include the transcription factor Nrf-2 which activates genes controlled by the antioxidant response element, and histone deacetylases of the sirtuin family and FOXO transcription factors. Such hormetic pathways stimulate the production of antioxidant enzymes, protein chaperones and neurotrophic factors. In several cases neurohormetic phytochemicals have been shown to suppress the disease process in animal models relevant to neurodegenerative disorders such as Alzheimer's and Parkinson's diseaess, and can also improve outcome following a stroke. We are currently screening a panel of biopesticides in order to establish hormetic doses, neuroprotective efficacy, mechanisms of action and therapeutic potential as dietary supplements.